Impact of Accounting Information System (AIS) Expenditure On Financial Performance of Selected Nigerian Deposit Money Banks (NDMBS) (2007-2022) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The emerging global economic scenario characterized by advancement in technology has brought about rapid changes in the banking industry. Management of various banking institutions in Nigeria relies heavily on information generated from the AIS employed by the firms.  Moreover, quality reports are keys to arrive at an ideal investment and efficient way for reporting company financial reports and take optimal decisions. This study examined the impact of AIS Expenditure on the performance of selected NDMBs. Specifically, the study examined the of effect of Accounting Information System expenditure on net profit, returns on equity and investment of selected NDMBsThe study adopted ex-post facto research design and data was sourced secondarily from the audited annual financial reports of selected NDMBs listed on the Nigerian Exchange Group for the period 2007-2022. The population of the study consisted of fourteen (14) NDMBs and a sample size of seven (7) was arrived at using purposive sampling technique to select banks whose annual report and accounts are readily accessible in the study period. Analytical techniques used in the study consisted of both descriptive and inferential statistics. Descriptive statistics employed includes minimum, maximum, mean and standard deviation while panel regression analysis was used to test the study hypotheses. Result of panel regression revealed that among the variables examined, only Operating expenses (OPEX), was found to be statistically significant in explaining the variation in net profit. The variable exhibited a positive effect on net profit, with a t-value of 2.6643 and a p-value of 0.0347. The overall influence of all tested independent variables Operating Expenses (OPEX), Human Resources Expenses (HREX), Information and Communication Technology Infrastructure (ICTIEX) and Research and Development Expenses (RDEX) on dependent variable on Net Profit was Adj. R-Squared 0.6257. This indicates that a unit increase in AIS expenditure is associated with a corresponding increase in 62.57% in net profit. The study therefore concluded that Accounting Information System expenditure has effect on the performance of Deposit Money Banks in Nigeria. It was therefore recommended that NDMBs should put mechanisms in place to aid further investments in the adoption of Accounting Information System.